Pharmacokinetics and Safety of Zidovudine, Lamivudine, and Lopinavir/Ritonavir in HIV-infected Children With Severe Acute Malnutrition in Sub-Saharan Africa: IMPAACT Protocol P1092. Issue 5 (May 2021) - Owor, Maxensia; Tierney, Camlin; Ziemba, Lauren; Browning, Renee; Moye, John; Graham, Bobbie; Reding, Christina; Costello, Diane; Norman, Jennifer; Wiesner, Lubbe; Hughes, Emma; Whalen, Meghan E.; et al.
Abstract : Background: Severe acute malnutrition (SAM) may alter the pharmacokinetics (PK), efficacy, and safety of antiretroviral therapy. The phase IV study, IMPAACT P1092, compared PK, safety, and tolerability of zidovudine (ZDV), lamivudine (3TC), and lopinavir/ritonavir (LPV/r) in children with and without SAM. Materials and methods: Children living with HIV 6 to <36 months of age with or without World Health Organization (WHO)-defined SAM received ZDV, 3TC, and LPV/r syrup for 48 weeks according to WHO weight band dosing. Intensive PK sampling was performed at weeks 1, 12, and 24. Plasma drug concentrations were measured using liquid chromatography tandem mass spectrometry. Steady-state mean area under the curve (AUC0–12h ) and clearance (CL/F) for each drug were compared. Grade ≥3 adverse events were compared between cohorts. Results: Fifty-two children were enrolled across 5 sites in Africa with 44% (23/52) female, median age 19 months (Q1, Q3: 13, 25). Twenty-five children had SAM with entry median weight-for-height Z-score (WHZ) −3.4 (IQR −4.0, −3.0) and 27 non-SAM had median WHZ −1.0 (IQR −1.8, −0.1). No significant differences in mean AUC0–12h or CL/F were observed ( P  ≥   0.09) except for lower 3TC AUC0–12h (GMR, 0.60; 95% CI, 0.4–1.0; P  = 0.047) at week 12, higher ZDV AUC0–12h (GMR, 1.52; 1.2–2.0; P  = 0.003) at week 24 in the SAM cohort compared with non-SAM cohort. Treatment-related grade ≥3 events did not differ significantly between cohorts (24.0% vs. 25.9%). Conclusion: PK and safety findings for ZDV, 3TC, and LPV/r support current WHO weight band dosing of syrup formulations in children with SAM.